Classical approach

Algebra Level 5

cyc ( a , b , c ) a 3 + b 3 a + 2 b \large \sum_{\text{cyc}(a,b,c)} \dfrac{a^3+b^3}{a+2b}

Given that a , b a,b and c c are positive numbers satisfying a 2 + b 2 + c 2 = 3 a^2+b^2+c^2=3 , find the minimum value of the expression above.

Submit your answer to 2 decimal places.


The answer is 2.00.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

P C
Sep 11, 2016

Relevant wiki: Cauchy-Schwarz Inequality

Using Cauchy-Schwarz we get c y c a , b , c a 3 + b 3 a + 2 b c y c a , b , c ( a 2 + b 2 ) 2 ( a + 2 b ) ( a + b ) \displaystyle\sum_{cyc}^{a,b,c}\frac{a^3+b^3}{a+2b}\geq \displaystyle\sum_{cyc}^{a,b,c}\frac{(a^2+b^2)^2}{(a+2b)(a+b)} By Titu's Lemma we have c y c a , b , c ( a 2 + b 2 ) 2 ( a + 2 b ) ( a + b ) 4 ( a 2 + b 2 + c 2 ) 2 c y c a , b , c ( a + b ) ( a + 2 b ) = 4 ( a 2 + b 2 + c 2 ) 2 3 ( a 2 + b 2 + c 2 + a b + a c + b c ) \displaystyle\sum_{cyc}^{a,b,c}\frac{(a^2+b^2)^2}{(a+2b)(a+b)}\geq\frac{4(a^2+b^2+c^2)^2}{\displaystyle\sum_{cyc}^{a,b,c}(a+b)(a+2b)}=\frac{4(a^2+b^2+c^2)^2}{3(a^2+b^2+c^2+ab+ac+bc)} c y c a , b , c a 3 + b 3 a + 2 b 4 ( a 2 + b 2 + c 2 ) 2 3 ( a 2 + b 2 + c 2 + a b + a c + b c ) \therefore\displaystyle\sum_{cyc}^{a,b,c}\frac{a^3+b^3}{a+2b}\geq\frac{4(a^2+b^2+c^2)^2}{3(a^2+b^2+c^2+ab+ac+bc)} Based on this inequality a b + b c + c a C S a 2 + b 2 + c 2 ab+bc+ca\stackrel{C-S}\leq a^2+b^2+c^2 c y c a , b , c a 3 + b 3 a + 2 b 4 ( a 2 + b 2 + c 2 ) 2 3 ( a 2 + b 2 + c 2 + a b + a c + b c ) 2 3 ( a 2 + b 2 + c 2 ) = 2 \Rightarrow\displaystyle\sum_{cyc}^{a,b,c}\frac{a^3+b^3}{a+2b}\geq\frac{4(a^2+b^2+c^2)^2}{3(a^2+b^2+c^2+ab+ac+bc)}\geq\frac{2}{3}(a^2+b^2+c^2)=2 So the minimum value is 2 and the equality obtains when a = b = c = 1 a=b=c=1

Nice problem,congratulations!Note that instead of using C-S in the first line of your solution,you could also do this(which is what i did): a 3 + b 3 a + 2 b = a 3 a + 2 b + b 3 a + 2 b = a 4 a 2 + 2 a b + b 4 a b + 2 b 2 \frac{a^3+b^3}{a+2b}=\frac{a^3}{a+2b}+\frac{b^3}{a+2b}=\frac{a^4}{a^2+2ab}+\frac{b^4}{ab+2b^2} ,and similarly for the other fractions.Then,you have a clear path ahead to apply Titu's Lemma.

Lorenc Bushi - 4 years, 9 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...